« La maternité refusée » dans La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres - Lévesque, Andrée (La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres, 1989)
Etude socio-historique des comportements sexuels de la femme au Québec sur une période de vingt ans. Les trois premiers chapitres traitent de la norme sociale qui s'impose aux femmes par rapport à la maternité et à la sexualité. Le reste concerne diverses formes de déviance sociale par rapport à trois catégories de comportements : le refus de la maternité (contraception, avortement, infanticide, abandon d'enfants); la maternité en dehors du mariage (mères célibataires); la sexualité commercialisée (prostitution).
Keywords: amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; cours; discipline; famille; his4523; histoire; hétérosexualité; justice reproductive; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sofia; thématiques

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Une femme - Ernaux, Annie (Collection Folio, 1987)
Annie Ernaux s'efforce ici de retrouver les différents visages et la vie de sa mère, morte le 7 avril 1986, au terme d'une maladie qui avait détruit sa mémoire et son intégrité intellectuelle et physique. Elle, si active, si ouverte au monde. Quête de l'existence d'une femme, ouvrière, puis commerçante anxieuse de «tenir son rang» et d'apprendre. Mise au jour, aussi, de l'évolution et de l'ambivalence des sentiments d'une fille pour sa mère : amour, haine, tendresse, culpabilité, et, pour finir, attachement viscéral à la vieille femme diminuée. «Je n'entendrai plus sa voix... J'ai perdu le dernier lien avec le monde dont je suis issue.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; approches et analyses; care; classisme; cours; discipline; europe; famille; france; inégalités; lit301N; littérature; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*

La naissance et la petite enfance en Nouvelle Angleterre à l'époque coloniale 1630-1750 - Bergamasco-Lenarda, Lucia (Revue d’histoire moderne et contemporaine, 1984)
Keywords: 1600-1699; 1700-1799; amériques; approches et analyses; colonialisme; colonisation britannique; condition de l'enfant; cours; discipline; enfance; famille; his4443; histoire; maternité; patriarcat; petite enfance; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

La Femme gelée - Ernaux, Annie (Gallimard, 1981)
Professeure de trente ans, mariée à un cadre, mère de deux enfants, elle habite un appartement agréable. Pourtant, c'est une femme gelée. C'est-à-dire que, comme des milliers d'autres femmes, elle a senti l'élan, la curiosité, toute une force heureuse présente en elle se figer au fil des jours entre les courses, le dîner à préparer, le bain des enfants, son travail d'enseignante.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; care; corps; corps féminin; cours; discipline; europe; famille; france; justice sociale; lit301N; littérature; maternité; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; écriture des femmes*